Exocrine Pancreatic Insufficiency in Children – Challenges in Management - Sankararaman S; Schindler T (Dove Medical Press, 2023)
Senthilkumar Sankararaman,1 Teresa Schindler2 1Division of Pediatric Gastroenterology, Department of Pediatrics, UH Rainbow Babies & Children's Hospital / Case Western Reserve University School of Medicine, Cleveland, OH, USA; 2Division of Pediatric Pulmonology, Department of Pediatrics, UH Rainbow Babies & Children's Hospital, Cleveland, OH, USACorrespondence: Senthilkumar Sankararaman, Division of Pediatric Gastroenterology, Hepatology & Nutrition, UH Rainbow Babies & Children's Hospital, Case Western Reserve University SOM, Cleveland, OH, USA, Tel +001 216-844-1765, Fax +001 216-844-8750, Email S.SankaraRaman@UHhospitals.orgAbstract: Cystic fibrosis (CF) is the leading etiology for exocrine pancreatic insufficiency (EPI) in children, followed by chronic pancreatitis, Shwachman-Diamond syndrome, and other genetic disorders. Management of EPI in children poses several unique challenges such as difficulties in early recognition, lack of widespread availability of diagnostic tests and limited number of pediatric-specific pancreatic centers. Pancreatic enzyme replacement therapy is the cornerstone of EPI management and in young children difficulties in administering pancreatic enzymes are frequently encountered. Patients with EPI also should be screened for fat-soluble vitamin deficiencies and receive appropriate supplementation. Among disorders with EPI in children, CF is the relatively well-studied condition, and most management recommendations for EPI in children come from expert consensus and conventional practice guidelines. The impact of EPI can be greater in children given their high metabolic demands and rapid growth. Early diagnosis and aggressive management of EPI prevent consequences of complications such as malnutrition, fat-soluble vitamin deficiencies, and poor bone health and improve outcomes. Management by multi-disciplinary team is the key to success.Keywords: exocrine pancreatic insufficiency, EPI, children, PERT, pancreatic enzymes